Evaluating Research Skills Development in a Colombian Undergraduate Foreign Language Teaching Program (2005)
ABSTRACT: The implementation of a research component in an undergraduate foreign language teaching programdirected towards preservice development is evaluated in this research. Results show that factors suchas course syllabi, professors' methodology, and administration leadership affect this curricular innovation.Despite difficulties, research skill development can be improved with the necessary training, support,and time for professors' understanding and collaboration.